Association of the Tripier myocutaneous flap to scapha cartilage graft: a surgical resource for reconstruction of full thickness defects of lower eyelids - Carlos Goyeneche Montoya; Mariane Campagnari; Andés Cánchica Cano; Andres Ordenes Evensen; Leonardo Gobetti; Osvaldo Saldanha; Eduard René Brechtbühl (Revista Brasileira de Cirurgia Plástica, 2020)
The reconstruction of the secondary lower eyelid to a resection of skin cancer is a challenging surgical procedure that must be carefully planned with regards to issues related to lamella and extension of the resection. We present the case of a 69-year-old male patient who, after oncologic resection, presented a total thickness defect greater than 60% in the lower eyelid. For reconstruction, it was indicated that the use of Tripier's unipedic myocutaneous flap with scapha cartilage graft produced favorable results, which confirms that it is worthwhile using these techniques when planning lower eyelid reconstruction.